MANAGEMENT MODEL OF SPITAK CITY LIBRARY (Bulletin of Armenian Libraries, 2023)
The presentation discusses management methods in the library sector, brief characteristics, the main directions of management and development of library work, and modern trends at the Spitak City Library. The talk presents the innovative leader program implementation, leadership skills, communication styles, professionalism, knowledge, the ability to use different information means, the stages of developing the innovative ideas and, projects, and making action plans.  The purpose of creating a public library as an education supporting institution, content and management methods, and the role in the digital age as a structure that ensures continuous education is also discussed.  Additionally, marketing as a modern tool of library management is discussed, including directions for effective implementation of library activities, tools that can expand the range of users and make the library more accessible, and changes that the library needs along with the development of new technologies and social networks.